2012
DOI: 10.1097/brs.0b013e31821fd21f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epidural Steroid Injections on Blood Glucose Levels in Patients With Diabetes Mellitus

Abstract: ESIs were noted to cause a significant increase in the blood glucose levels in diabetics. There was no correlation between preinjection diabetic control, represented by hA(1c) levels, and postinjection response. Diabetics who are candidates for ESI should be counseled that a blood glucose increase may be apparent post intervention, but effects should not last longer than approximately 2 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 14 publications
1
45
0
2
Order By: Relevance
“…It has been demonstrated that a significant elevation in blood glucose levels occurs after epidural steroid injections, a common treatment for patients with lumbar radiculopathy [59] . A transient rise of nearly 80% occurred, however the serum glucose level normalized with 48 h of the procedure.…”
Section: Nonsurgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that a significant elevation in blood glucose levels occurs after epidural steroid injections, a common treatment for patients with lumbar radiculopathy [59] . A transient rise of nearly 80% occurred, however the serum glucose level normalized with 48 h of the procedure.…”
Section: Nonsurgical Treatmentmentioning
confidence: 99%
“…A transient rise of nearly 80% occurred, however the serum glucose level normalized with 48 h of the procedure. Diabetic patients should be advised that a temporary elevation in blood glucose is likely post injection [59] .…”
Section: Nonsurgical Treatmentmentioning
confidence: 99%
“…There are studies that suggest a possible systemic effect of steroids used in ESI. In these studies investigating the systemic effects of epidural and intraarticular glucocorticoid injections, a significant increase was reported in the glucose levels of diabetic and nondiabetic patients (27)(28)(29). In our study, a clinically insignificant increase in WBC values was found after both groups received ESI.…”
Section: Discussionmentioning
confidence: 37%
“…W większości badań opisano przejściowy istotny wzrost stężenia glukozy we krwi i powrót glikemii do wartości prawidłowych po 2-3 dniach po iniekcji [61][62][63].…”
Section: Efekt Diabetogenny Glikokortykosteroidówunclassified
“…Bardzo interesujące wydają się próby zastosowania tej grupy leków inkretynowych w prewencji zaburzeń tolerancji glukozy u osób przyjmujących GS. Wykazano, że wlew eksenatydu zapobiegał dysfunkcji komórek wysp trzustkowych i hiperglikemii wywołanej krótkoterminowym podaniem GS [62]. Pojawiły się również doniesienia o korzystnym efekcie stosowania inhibitorów dipeptydylopeptydazy 4 (DPP-4) w cukrzycy posteroidowej [70,71].…”
Section: Leczenie Cukrzycy Posteroidowejunclassified